PENINGKATAN HASIL BELAJAR SENI RUPA DENGAN MENCIPTAKAN KARYA SENI DARI KERTAS BEKAS MENGGUNAKAN MODEL PROJECT BASED LEARNING DI KELAS V B SDN 04 PAUH KOTA PADANG - Berliana Syavira; Mansurdin, Mansurdin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the low learning outcomes of students who think that learning Fine Arts is learning to draw and sing only. This study aims to describe the improvement of fine arts learning outcomes by creating works of art from used paper using the project-based learning (PjBL) model in class V B SDN 04 Pauh Kota Padang. This type of research is a classroom action research (PTK) with qualitative and quantitative approaches. Implemented in 2 cycles, each cycle consists of 2 meetings. The subjects of this research 27 students. The results showed: First, the teaching module aspect obtained an average of 83.33% (B) increased in cycle II 91.66% (SB). Second, the results of the implementation of cycle I on the teacher aspect obtained an average percentage of 87.50% (B), increasing in cycle II to 93.75% (SB). Third, the results of the implementation of cycle I on the aspects of students obtained an average of 87.50% (B), increasing in cycle II to 93.75% (SB). Fourth, the learning outcomes of students in cycle I obtained an average of 73.53 (C), increasing in cycle II to 87.14 (B). It can be concluded that the Project Based Learning (PjBL) model can improve the learning outcomes of fine arts by creating artworks from used paper in class V B SDN 04 Pauh Padang City.